Determination of soluble hexavalent chromium in samples of Portland cement from Brazilian cement manufacturers - Vanessa Zuliani; Rafaela Boni Serata; Juliana de Carvalho Izidoro (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Urbanization growing is nowadays highlighted in the big cities. Therefore, it is necessary to increase the production of cement, which is used in several areas of civil construction, to supplement the growing demand. Thus, the objective of this study was to determine the content of hexavalent soluble chromium in Portland cement samples from different cement industries in São Paulo state, Brazil, since this chemical species can cause adverse health effects as well as being a potential human carcinogenic for those who manipulate it. In Brazil, the emission of Cr6+ in the cement has no restrictions, since there is no current Brazilian law that determines the maximum concentration of it, whereas, in Europe, the current law 2003/53/EC establishes a maximum of 2 mg.kg-1. So, the Cr6+ content for different cement samples was determined by spectrophotometry based on the European standard EN196-10/2006. It was found by the analysis that among all types of cement produced in São Paulo, the only one that did not exceed the standard limit was the CP III, probably because this kind of cement has a high concentration of additions in its composition, responsible for diluting thereby chromium content. The other types of cement exceeded the established limit. It was concluded that Brazil urgently needs a law to regulate the hexavalent soluble chromium emission present in Portland cement to minimize the environmental and health effects that the cement out of specification may cause.